New technologies for electrochemical applications - Naushad, Mu; Rajendran, Saravanan; Al-Enizi, Abdullah M. (Boca Raton, FL : CRC Press LLC, 2020)
The field of electrochemistry is exploring beyond its basic principles to innovation. New Technologies for Electrochemical Applications presents advancements in electrochemical processes, materials, and technology for electrochemical power sources such as batteries, supercapacitors, fuel cells, hydrogen storage and solar cells. It also examines various environmental applications such as photo electrochemistry, photosynthesis, and coating. Organized to give readers an overview of the current field in electrochemical applications, this book features a historical timeline of advancements and chapters devoted to the topics of organic material and conducting polymers for electrochemical purposes. Established experts in the field detail state-of-the-art materials in biosensors, immunosensors, and electrochemical DNA. This edited reference is a valuable resource for graduate and post-graduate students, and researchers in disciplines such as chemistry, physics, electrical engineering and materials science.
OCLC-licensed vendor bibliographic record.
Keywords: Electrochemistry; SCIENCE / Chemistry / General; SCIENCE / Chemistry / Physical & Theoretical; SCIENCE / Chemistry / Industrial & Technical